Endobronchial lipoma - Lakshitha Anbazhakan; Asad Ullah Khan; Rohit Munagala; Rabih Bechara; Islam Elhelf; Nikhil Patel; Nagla Abdel Karim (University of São Paulo, 2022)
Endobronchial lipomas are rare benign lung tumors that can cause bronchial obstruction and parenchymal damage. While an uncommon etiology, they are often misdiagnosed due to a clinical presentation similar to obstructive pulmonary pathologies such as COPD and asthma. Upon review of English-language literature, under 50 cases of endobronchial lipomas were documented in the prior 10 years (2011-2021). There are no clear guidelines regarding the management of this particular entity, but typically interventional debulking is the treatment of choice. Here we present another unique case of endobronchial lipoma along with our diagnostic and therapeutic methodology. The patient underwent bronchoscopic debulking via a cryotherapy probe. Based on the histopathologic analysis, a diagnosis of endobronchial lipoma was made. Endobronchial lipomas must remain in any clinician's differential when a patient presents with dyspnea. We report the unique location of this lipoma based on our literature review and the importance of investigating endobronchial lesions due to a possible diagnosis of endobronchial lipoma.